Faktor-Faktor yang Mempengaruhi Keputusan Membeli Sandal di Surabaya: Harga, Distribusi, dan Gaya Hidup - Maytita Tri Hardiyanti; Didit Darmawan (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This study aims to analyse the effect of price, distribution, and lifestyle on purchasing decisions for Swallow sandals in Surabaya. The research method uses a quantitative approach by collecting data through questionnaires from 100 respondents purposely selected from the Surabaya community who have purchased Swallow sandals. The research findings show significant managerial implications, including the need for distribution channel management to pay attention to distributor decisions on sales force services. Improving service quality and product availability at the right time are key to strengthening consumer trust in distribution channels. Understanding and utilising consumer lifestyle values in marketing strategies is also important. Awareness of the positive impact of lifestyle on purchasing decisions can help design marketing that is more in line with consumer preferences, including the addition of product variations that reflect the target market's lifestyle to increase product appeal and expand market share. With these findings, companies can optimise marketing strategies and product management, increase consumer satisfaction, strengthen brand loyalty, and achieve long-term success in the market